Investigations on the effect of low temperature cooling on the phase transformations of the EN AW 7075 alloy. Issue 1 (October 2021) - Stoicanescu, M; Crisan, A; Bedo, T; Varga, B; Milosan, I; Peter, I
Abstract: Al-based alloys are very challenging materials, especially in applications where energy and mass reduction are required. In this scenario, EN AW 7075 Al-based alloy can be considered of high interest for different large and thick products. One of the many fields of interest where large geometry dynamic is present is, for example, aerospace, where the alloy structural stability in different conditions is very important. In this paper, the main attention is oriented toward the structural investigation of the EN AW 7075 Al-based alloy in different condition, by differential scanning calorimeter and dilatometry analysis, in order to be able to propose it, as a suitable material for aerospace component production. The analysis on the conditioned and un-conditioned materials has been used to assess the alloy's performance and to control the evolution of the alloy properties, in specific conditions, important aspect for the targeted application. Some data on the mechanical behaviour of the alloy integrate the study.